Deletion of gene encoding the nucleoid-associated protein H-NS unmasks hidden regulatory connections in El Tor biotype Vibrio cholerae - Russell, Raedeen (Microbiology (Reading), 2018)
Hypervirulent atypical El Tor biotype Vibrio cholerae O1 isolates harbour mutations in the DNA-binding domain of the nucleoid-associated protein H-NS and the receiver domain of the response regulator VieA. Here, we provide two examples in which inactivation of H-NS in El Tor biotype vibrios unmasks hidden regulatory connections. First, deletion of the helix-turn-helix domain of VieA in an hns mutant background diminished biofilm formation and exopolysaccharide gene expression, a function that phenotypically opposes its phosphodiesterase activity. Second, deletion of vieA in an hns mutant diminished the expression of σ(E), a virulence determinant that mediates the envelope stress response. hns mutants were highly sensitive to envelope stressors compared to wild-type. However, deletion of vieA in the hns mutant restored or exceeded wild-type resistance. These findings suggest an evolutionary path for the emergence of hypervirulent strains starting from nucleotide sequence diversification affecting the interaction of H-NS with DNA.